Reaction of enzymes with starch granules: kinetics and products of the reaction with glucoamylase - Kimura, A.; Robyt J.F.
The reaction of glucoamylase with starch granules from seven botanical sources (waxy maize, maize, barley, tapioca, amylomaize-7, shoti, and potato)and with four potato starches modified with acid in four types of alcohols (methanol, ethanol, 2-propanol, and 1-butanol)were studied using three concentrations of enzyme (2, 20, and 200 units mL-t). The kinetics of the formation of o-glucose were followed over 32 h for the three enzyme concentrations. The starches showed a wide degree of variance in their susceptibility to enzyme hydrolysis. They divided into three groups: waxy maize starch was the most susceptible being converted into 50, 95, and 98 (percent)D-glucose in 32 h for the three concentrations of enzyme, respectively; an intermediate group (barley, maize, and tapioca starches)was converted into 10-15, 60, and 75-80 (percent)D-glucose in 32 h for the three concentrations of enzyme, respectively; and the third and least susceptible group (amylomaize-7, shoti, and potato starches)was converted into 2-8, 9-16, and 13-21(percent)D-glucose in 32 h for the three concentrations of enzyme, respectively. The percent conversion for the modified potato starches was proportional to the amount of enzyme and the degree of modification. The 100X (200 U mL-t)amount of enzyme gave 13, 17, 21 and 27(percent)D-glucose in 32 h for potato starch modified in the four alcohols, respectively. The number and size of the granules were determined over 32 h of reaction using 10X (20 U mL-) enzyme for waxy maize starch and 100X enzyme for the other starches. The number of granules for waxy maize, barley, maize, and tapioca starches significantly increased in the first part of the reaction and then decreased; this was paralleled by a decrease of 40-50(percent)in the size of the granules. The number and size of the potato and shoti starch granules did not change very significantly and the number and size of amylomaize-7 starch granules decreased slightly butsteadily to about 25(percent)of the number and size of the native granules. The morphologies of the granules during reaction were studied by scanning electron microscopy. Extensive conversion into 50(percent)D-glucose for the starches in the first two groups showed the classical "Swiss cheese" shell structure with many deep holes into the granules. The least susceptible starches in the third group did not show much change in morphology, except for some minor surface pitting.
Keywords: ENZYMES; STARCH GRANULES; GLUCOAMYLASE